1992
DOI: 10.1099/0022-1317-73-11-2949
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP-mediated inhibition of vesicular stomatitis virus and herpes simplex virus replication in mouse macrophage-like cells

Abstract: In this study, we have analysed the effects of cAMP inducers on the multiplication of vesicular stomatis virus (VSV) and herpes simplex virus type 1 (HSV-1) in mouse macrophage-like cells. The addition ofdibutyryl cAMP (dB-cAMP) or cholera toxin to resting peritoneal macrophages aged in vitro or P388D1 cells resulted in a 10-to 100-fold reduction of VSV yield compared to control cultures. In contrast, no cAMP-dependent inhibition was found in VSV-infected L929 cells. In macrophage-like cells, the dB-cAMP-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Several studies have shown that viral replication is regulated (enhanced or inhibited) by cAMP signaling. For example, the replication of hepatitis C and human immunodeficiency viruses is enhanced by modulating cellular levels of cAMP [ 40 , 41 ]. In contrast, replication of vesicular stomatitis and herpes simplex viruses is inhibited by cAMP signaling [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that viral replication is regulated (enhanced or inhibited) by cAMP signaling. For example, the replication of hepatitis C and human immunodeficiency viruses is enhanced by modulating cellular levels of cAMP [ 40 , 41 ]. In contrast, replication of vesicular stomatitis and herpes simplex viruses is inhibited by cAMP signaling [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Replication of HSV can be affected by CAMP. The virus has been shown to be inhibited by cAMP in macrophages (Borghi et al, 1992), while on the other hand there is an increase in permissiveness to the virus in ND cells, which are derived from the fusion of dorsal root ganglion neurons with a neuroblastoma cell line (Wheatley et al, 1992). However, since there was no difference in virus yield from neurons either with or without CPTcAMP this explanation is unlikely, and the increase in survival in stl7/PKAcat-infected cells must be due to PKAcat activity.…”
Section: Discussionmentioning
confidence: 99%